Transient regression and fluctuation of bilateral adrenal masses: a rare presentation of primary adrenal lymphoma - Maliki, Aminnur H.; Baghawi, Anita (International Surgery Journal, 2022)
Primary adrenal lymphoma is a rare form of extra-nodal lymphoma which scarcely reported in the literature reviews. We describe such a case who presented with fluctuation in the sizes of bilateral adrenal masses. A 61-year-old lady who presented with a history of right flank discomfort with no other associated symptoms. Initial imaging showed bilateral adrenal masses. She was evaluated and excluded for possibilities of pheochromocytoma, cortical carcinoma and secondary tumour deposits. Interestingly, a consecutive of contrast-enhanced computed tomography images showed transient regression and fluctuation of bilateral adrenal masses, which making the diagnosis became more challenging. A confirmatory histological diagnosis was obtained via imaging-guided biopsy which revealed diffuse large B cell lymphoma. Unfortunately, the patient was reluctant to receive chemotherapy and eventually lost to follow-up. Diagnosing a primary adrenal lymphoma can be challenging due to its rarity and requires high index of suspicion for timely diagnosis and treatment.